EFFECT OF EXTRACTIVE CONTENTS ON NATURAL RESISTANCE OF FIVE DIFFERENT WOOD TO XILOPHAGAUS TERMITES ATTACK - Paes, Juarez Benigno (2016)
When man stopped being nomadic, he had to adapt to new conditions, and started employing wood for energy, hunting and defense instruments and miscellaneous constructive elements. Since then, in the light of usages and rapid growth, the importance of wood has been increasing, primarily by their exploitation assaults less the environment when compared to other non-renewable materials. Although there are several researches about Eucalyptus and Pinus, but studies with other species are incipient mainly about the extractive effects on the wood natural resistance. Thus, this research aimed to assess the influence of extractive contents with the natural resistance of Acacia mangium, Casuarina sp. Eucalyptus cloeziana, Corymbia torelliana and Tectona grandis woods to Nasutitermes corniger xylophagous termite, species of frequent occurrence in several regions in Brazil. From each species, test samples were taken, with dimensions of 2.00 x 10.16 x 0.64 (radial x longitudinal x tangential) in four positions in the medulla-sapwood direction (internal core, intermediate core, outer core and sapwood). The woods were exposed to the action of termites for 45 days in a food preference assay. The samples not selected for the test with termites were turned into sawdust and the extractive contents were obtained by using the fraction which passed through the sieve 40 and was retained in mesh 60. The natural resistance has not been linked to extractive levels present in the wood. The resistance of wood varied in medulla-sapwood direction, with default variable for each species. The more resistant timbers were Tectona grandis and Corymbia torelliana and the most deteriorated was Acacia mangium.